The Evaluation of the College Library Information Systems Usage in Malaysia - Sobri, A'lya Safiah Binti Ahmad (Edulib, 2021)
Libraries now need to be cooperated along with the use of information systems. This information system has been widely applied and has succeeded in helping library services as well as facilitating library management while at the same time attracting more people to use the library which will bring various benefits to them. The DeLone and McLean model is a model that has 6 evaluation variables, namely: system quality, information quality, service quality, system use, user satisfaction and net benefits. The use of this model can help determine the success and success of the information system contained in the Universiti Malaysia Pahang library. With the use of this model, it is hoped that it will be known where the stage of this library information system is. The results of the study show that the quality and success of information systems plays an important role in ensuring that user satisfaction is achieved. Basically, users feel happy and satisfied with the information system provided. And it is hoped that this study can be a guide to making good decisions for the library and be a guide for future research.